Migration and maturation pattern of fetal enteric ganglia: A study of 16 cases - Ranjana Bandyopadhyay; Uttara Chatterjee; Sanjay K Bandyopadhyay; Ashoke K Basu (Wolters Kluwer Medknow Publications, 2011)
Aims: To study the migration and developmental pattern of ganglion cells in fetuses aged 9-21 weeks, and to document whether the migration was occurring circumferentially equally in the entire axis or if there were discrepancies in different portions at the same level. Settings and Design: The hypothesis regarding the pathogenesis of Hirschsprung's disease mainly revolves around two schools. One is the single gradient migration of ganglia and the other is a dual gradient migration theory. Understanding the embryological development of enteric ganglia is necessary to study the pathogenesis of intestinal innervation disorders. Materials and Methods: We studied the development of intestinal ganglia in fetuses aged 9-21 weeks. Serial longitudinal sections from the colon were studied, the first one including the squamo-columnar junction, for the presence and the nature of ganglion cells with Hematoxylin and Eosin, and neurone-specific enolase immunostaining. Transverse sections from proximal gut were studied in a similar fashion. Thus, we evaluated the migration pattern as well as the nature of ganglia in the fetuses. We also measured the length of distal aganglionic segment in these growing fetuses. Results: We noted that ganglion cells appear first in the myenteric plexus followed by deep and superficial submucous plexus. We also found evidences in favor of dual migration theory, and the distal aganglionic segment varies around the circumference of the rectal wall. Conclusions: We got evidences in support of a dual migration pattern of intestinal ganglion cells. The level of distal aganglionic segments when measured from squamo-columnar junction varied with the age of gestation and the length was incongruous. The description of distal aganglionic segment may help surgeons while taking biopsies or during operative procedures.